TGF-β1/Smads and miR-21 in Renal Fibrosis and Inflammation - Agnieszka Loboda; Mateusz Sobczak; Alicja Jozkowicz; Jozef Dulak (Mediators of Inflammation)
Renal fibrosis, irrespective of its etiology, is a final common stage of almost all chronic kidney diseases. Increased apoptosis, epithelial-to-mesenchymal transition, and inflammatory cell infiltration characterize the injured kidney. On the molecular level, transforming growth factor-β1 (TGF-β1)-Smad3 signaling pathway plays a central role in fibrotic kidney disease. Recent findings indicate the prominent role of microRNAs, small noncoding RNA molecules that inhibit gene expression through the posttranscriptional repression of their target mRNAs, in different pathologic conditions, including renal pathophysiology. miR-21 was also shown to play a dynamic role in inflammatory responses and in accelerating injury responses to promote organ failure and fibrosis. Understanding the cellular and molecular bases of miR-21 involvement in the pathogenesis of kidney diseases, including inflammatory reaction, could be crucial for their early diagnosis. Moreover, the possibility of influencing miR-21 level by specific antagomirs may be considered as an approach for treatment of renal diseases.